1973
DOI: 10.1111/j.1550-7408.1973.tb03585.x
|View full text |Cite
|
Sign up to set email alerts
|

Fine Structure of Gametogony and Oocyst Formation in Sarcocystis sp. in Cell Culture

Abstract: SYNOPSIS Fine structure of gametocytes and oocyst formation of Sarcocystis sp. from Quiscalus quiscula Linnaeus grown in cultured embryonic bovine kidney cells was studied. Microgametocytes measured up to ∼5 μm diameter. During nuclear division of the microgametocyte, dense plaques were found adjacent to the nucleus just beneath the pellicle; occasionally microtubules were present within these plaques. These microtubules subsequently formed 2 basal bodies with a bundle of 4 microtubules between them. Microgame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

1975
1975
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…In their ultrastructural study on Giardia lamblia, Reiner et al (1990) showed that a regulated pathway of transport and secretion of cyst wall antigens via a novel class of large, osmiophilic secretory vesicles, the encystation-specific vesicles, was assembled during encystation. Vetterling et al (1973) and Zaman and Colley (1975) observed that the wall-forming bodies in some species of Sarcocystis gave rise to the outer layer of the oocyst wall. The inclusion-like bodies (SAI) lining the rim of the cytoplasm in our study could be similar to the encystation secretory vesicle in Giardia and to the wall-forming bodies in coccidians previously mentioned by other workers and may perform similar functions.…”
Section: Discussionmentioning
confidence: 96%
“…In their ultrastructural study on Giardia lamblia, Reiner et al (1990) showed that a regulated pathway of transport and secretion of cyst wall antigens via a novel class of large, osmiophilic secretory vesicles, the encystation-specific vesicles, was assembled during encystation. Vetterling et al (1973) and Zaman and Colley (1975) observed that the wall-forming bodies in some species of Sarcocystis gave rise to the outer layer of the oocyst wall. The inclusion-like bodies (SAI) lining the rim of the cytoplasm in our study could be similar to the encystation secretory vesicle in Giardia and to the wall-forming bodies in coccidians previously mentioned by other workers and may perform similar functions.…”
Section: Discussionmentioning
confidence: 96%
“…The male gamete (microgamete) is flagellated and swims to the female gamete (macrogamete) to carry out fertilization. The anterior end of apicomplexan microgametes is pointed and contains three basal bodies in close proximity to the apical pole (116,137,158,181). These basal bodies nucleate two or three flagella that extend past the nucleus and away from the apical end.…”
Section: Microtubules In the Apicomplexa Organizationmentioning
confidence: 99%
“…In some species this third flagellum is present only in rudimentary form as a band of microtubules that extends along the length of the gamete. In contrast to the atypical centrioles observed in other stages, the basal body of male gametes has a typical triplet microtubule structure with ninefold symmetry and the flagellar axoneme contains a conventional 9ϩ2 arrangement of doublet microtubules surrounding the central pair of microtubules (137,(158)(159)(160)181). In Plasmodium, genesis of the basal bodies involves an intermediate 9ϩ1 singlet form similar to the centrioles in other apicomplexans (157).…”
Section: Microtubules In the Apicomplexa Organizationmentioning
confidence: 99%
“…including S. singaporensis only a single type of wallforming-like body present, also referred to as "dense granules" or "bodies" (Vetterling et al, 1973;Entzeroth et al, 1985). Viewing the fine structural evidences available to date, the species-specificity of their configuration is certain.…”
Section: Discussionmentioning
confidence: 99%
“…Viewing the fine structural evidences available to date, the species-specificity of their configuration is certain. Less certain (see Entzeroth et al, 1985) is their claimed role in wall formation (Vetterling et al, 1973;Zaman & Colly, 1975). A seemingly anlagen of wall-forming-like bodies within the perimeter of a Golgi-like organelle recalls the suggested role of the Golgi system in the formation of type 1 wall-forming bodies in eimerians (Scholtyseck et al, 1971).…”
Section: Discussionmentioning
confidence: 99%